Information management : strategies for gaining a competitive advantage with data - McKnight, William (Consultant) (Waltham, Massachusetts : Morgan Kaufmann, 2014)
This book covers the following topics: the importance of information management and analytics to business, and how data warehouses are used; the technologies and data that advance an organization, and extend data warehouses and related functionality; Big Data and NoSQL, and how technologies like Hadoop enable management of new forms of data; agile development, modern business intelligence, and organizational change management.
1. You're in the business of information -- 2. Relational theory in practice -- 3. You're in the business of analytics -- 4. Data quality : passing the standard -- 5. Columnar databases -- 6. Data warehouses and appliances -- 7. Master data management : one chapter here, but ramifications everywhere -- 8. Data stream processing : when storing the data happens later -- 9. Data virtualization : the perpetual short-term solution -- 10. Operational big data : key-value, document, and column stores : hash tables reborn -- 11. Analytical big data : hadoop : analytics at scale -- 12. Graph databases : when relationships are the data -- 13. Cloud computing : on-demand elasticity -- 14. An elegant architecture where information flows -- 15. Modern business intelligence : collaboration, mobile, and self-service : organizing the discussion and tethering the user to information -- 16. Agile practices for information management -- 17. Organizational change management : the soft stuff is the hard stuff.
Print version record.
Includes bibliographical references and index.
Keywords: Database management; Big data; Data mining; COMPUTERS -- Desktop Applications -- Databases; COMPUTERS -- Database Management -- General; COMPUTERS -- System Administration -- Storage & Retrieval; Data mining; Big data; Database management; Data Mining; Electronic books